Village Governance System in Indonesia - Wardana, Rian Ismi; Frinaldi, Aldri; Magriasti, Lince; Naldi, Hendra (Universitas Pahlawan Tuanku Tambusai, 2026)
This article examines the dynamics of the village governance system in Indonesia within the context of decentralization following the enactment of Law Number 6 of 2014 on Villages. Although numerous studies have discussed village autonomy, fiscal decentralization, and Village Fund management, existing literature tends to focus on fragmented aspects such as financial accountability or leadership, without providing a comprehensive synthesis of institutional structure, authority distribution, participatory governance, and implementation challenges within a unified analytical framework. Therefore, this literature review is necessary to bridge this gap by offering an integrative analysis of how regulatory frameworks, institutional capacity, and socio-political dynamics interact in shaping village governance outcomes. Utilizing a qualitative literature study approach, this article analyzes legal documents, academic publications, and empirical research findings related to village governance. The findings indicate that while villages are normatively granted broad authority and increased fiscal resources, implementation remains constrained by weak administrative capacity, limited community participation, and persistent elite dominance. However, innovative practices such as administrative digitalization and transparency initiatives demonstrate significant potential when supported by strong leadership and institutional reform. This study concludes that strengthening village governance requires a holistic strategy that integrates regulatory refinement, differentiated institutional capacity development, participatory oversight mechanisms, and sustainable community empowerment..